Active energy ray curable resin composition
By integrating a polyglycerin fatty acid ester and a (meth)acryloyl group-containing monomer into the resin composition, the challenge of achieving simultaneous antibacterial, antifogging, and antistatic properties is addressed, resulting in a cured product with superior performance in these areas.
Patent Information
- Application Number
- JP2022007630
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-01-21
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-01-21
AI Technical Summary
Conventional active energy ray-curable resin compositions struggle to simultaneously impart antibacterial, antifogging, and antistatic properties to base materials.
Incorporating a specific polyglycerin fatty acid ester and a specific (meth)acryloyl group-containing polymerizable monomer into an active energy ray-curable resin composition, along with a photoinitiator, to achieve a cured product with enhanced antibacterial, antifogging, and antistatic properties.
The resulting cured product exhibits excellent antibacterial, antifogging, and antistatic properties, demonstrating strong performance across all three functionalities.
Smart Images

Figure 0007612622000004 
Figure 0007612622000001 
Figure 0007612622000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition that is cured by active energy rays and a cured resin product having antibacterial, antifogging and antistatic properties. [Background technology]
[0002] Conventionally, for the purpose of imparting antibacterial properties, antifogging properties, or antistatic properties to substrates such as polymeric materials and glass, the substrate surface has been coated with an active energy ray-curable resin composition by a method such as painting, and then irradiated with active energy rays to provide a cured product (cured film: coating layer).
[0003] As a technique for imparting antibacterial properties, for example, an active energy ray curable resin composition containing a polyfunctional (meth)acrylate and an organic nitrogen sulfur-based antibacterial agent (Patent Document 1) is disclosed. As a technique for imparting antifogging properties, for example, an active energy ray curable antifogging composition containing a urethane (meth)acrylate resin and an aqueous unsaturated group-containing compound, in which a polyol compound, a polyisocyanate compound, and a hydroxyl group-containing (meth)acrylate compound are essential reaction raw materials (Patent Document 2) is disclosed. As a technique for imparting antistatic properties, a coating agent composition containing an alkali metal salt, a specific acrylamide derivative, and a curable compound having two or more active energy ray polymerizable groups in the molecule (Patent Document 3) is disclosed.
[0004] Although these conventional techniques can provide any one of antibacterial properties, antifogging properties, and antistatic properties, it is difficult to provide all three properties at the same time. Therefore, there is a demand for an active energy ray-curable resin composition that can provide all of antibacterial properties, antifogging properties, and antistatic properties. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2020-139158 A [Patent Document 2] Patent Publication No. 2021-46483 [Patent Document 3] JP 2006-152130 A Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide an active energy ray-curable resin composition which is capable of giving a cured product which is excellent in all of antibacterial properties, antifogging properties, and antistatic properties. [Means for solving the problem]
[0007] As a result of intensive research into solving the above problems, the present inventors have found that the above problems can be solved by blending a specific polyglycerol fatty acid ester and a specific polymerizable monomer having a (meth)acryloyl group in an active energy ray-curable resin composition. Based on these findings, the present inventors have further researched and completed the present invention. That is, the present invention has the following configuration. [1] An active energy ray-curable resin composition comprising the following (A) to (D): (A): Polyglycerol fatty acid ester in which the average degree of polymerization of the constituent polyglycerol is 2 to 3 and the carbon number of the main constituent fatty acid is 10 to 18. (B): one or more selected from the group consisting of dialkyl(meth)acrylamide, dialkylaminoethyl(meth)acrylamide, dialkylaminopropyl(meth)acrylamide, dialkylaminoethyl(meth)acrylate, and dialkylaminopropyl(meth)acrylate (C): A polymerizable monomer having four or more ethylene glycol groups and one or more (meth)acryloyl groups in one molecule. (D): Photopolymerization initiator [2] The active energy ray-curable resin composition according to the above [1], further comprising the following (E): (E): A polymerizable monomer and / or oligomer having a (meth)acryloyl group other than (B) and (C) described in [1] above. [3] A cured resin product obtained by irradiating the active energy ray-curable resin composition according to the above [1] or [2] with active energy rays. Effect of the Invention
[0008] The active energy ray-curable resin composition of the present invention is cured by active energy rays, and the resulting cured product exhibits the effects of being excellent in all of antibacterial properties, antifogging properties, and antistatic properties. [Brief description of the drawings]
[0009] [Figure 1] A cylindrical, bottomless beaker with a sloped top surface for evaluating anti-fogging properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The active energy ray-curable resin composition of the present invention (hereinafter also referred to as "the resin composition of the present invention") is usually in a liquid or paste form, and is cured by active energy rays.
[0011] The average degree of polymerization of (A): polyglycerol fatty acid ester (hereinafter also referred to as "component A") used in the present invention, in which the average degree of polymerization of the constituent polyglycerol is 2 to 3 and the carbon number of the main constituent fatty acid is 10 to 18, is 2 to 3, preferably 2. When there is a nominal value by the manufacturer of the polyglycerol fatty acid ester, this value is used as the average degree of polymerization. When there is no nominal value, the average degree of polymerization is determined by analyzing the composition of the polyglycerol (i.e., the polyol composition) constituting the polyglycerol fatty acid ester. The method is shown in the following steps (1) to (3).
[0012] (1) Sample preparation First, the test sample is decomposed into fatty acids and polyols by saponification decomposition treatment. Specifically, 2.0 g of the test sample is weighed into a saponification flask, 30 mL of 0.5 mol / L potassium hydroxide-ethanol standard solution is added to it, a condenser is attached to the flask, and the temperature is adjusted within a range of about 70 to 80 ° C. while occasionally shaking and mixing, and the refluxed ethanol does not reach the top of the condenser, and the mixture is gently heated for about 1 hour, and then the flask is transferred to a separatory funnel while washing it with 40 to 50 mL of hot water, 40 to 50 mL of water, and 100 mL of hexane in order. About 5 mL of 10% hydrochloric acid is added to this separatory funnel, the separatory funnel is shaken, 50 mL of hexane is added to it, and the mixture is further shaken and then left to stand. The separated lower layer is taken into a beaker, the pH is adjusted with 0.5 mol / L potassium hydroxide solution to neutralize it, and the beaker is left to stand in a ventilated dryer at 60 ° C. to dehydrate it. Once completely dehydrated, add 5-10mL of methanol in 2-3 portions, stir the contents, and allow to filter naturally. Transfer the filtrate to a flask and remove the methanol using an evaporator.
[0013] (2)Measurement method Next, 50 mg of the concentrate obtained is weighed out, and 1 to 2 mg of pyridine (special grade reagent; Fujifilm Wako Pure Chemical Industries, Ltd.) is added to it, mixed and dissolved. 0.5 mL of 1,1,1,3,3,3,-hexamethyldisilazane (Tokyo Chemical Industry Co., Ltd.) is added to it and mixed, and further 0.1 mL of trifluoroacetic acid (special grade Wako; Fujifilm Wako Pure Chemical Industries, Ltd.) is added and mixed. After leaving it for about 1 minute, the polyol composition is analyzed using GC (gas chromatography) under the following conditions. ≪GC analysis conditions≫ Equipment: Gas chromatogram (model: GC-2010Plus; Shimadzu Corporation) Data processing software (model: GCsolution version 2.4; Shimadzu Corporation) Column (Model: Ultra ALLOY-TRG; P / N: UATRG-30M-0.1F; manufactured by Frontier Labs) Column oven conditions: initial temperature 100°C (1 min); heating rate 15°C / min; final temperature 365°C (11 min) Sample injection volume: 1.0 μL Carrier gas: Nitrogen
[0014] (3) Quantification After the analysis, the peak areas of the peaks corresponding to each component of the test sample recorded on the chromatogram by the data processing software are measured using an integrator, the polyol composition is determined as an area percentage based on the measured peak areas, and the weight average value of the polymerization degree of each component is calculated to obtain the average polymerization degree.
[0015] The "main constituent fatty acid" in component A refers to a fatty acid that occupies 50% by mass or more, preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more of the total fatty acids constituting the polyglycerol fatty acid ester (100% by mass). Therefore, for example, a polyglycerol fatty acid ester in which the main constituent fatty acid is a fatty acid having 10 to 18 carbon atoms means that the fatty acid having 10 to 18 carbon atoms occupies 50% by mass or more of the total fatty acids constituting the polyglycerol fatty acid ester (100% by mass).
[0016] Examples of fatty acids having 10 to 18 carbon atoms include capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid, elaidic acid, linoleic acid, linolenic acid, etc., and preferred are fatty acids having 12 to 16 carbon atoms (e.g., lauric acid, myristic acid, palmitic acid, etc.). At least one of these fatty acids can be used, or two or more of them can be used in combination.
[0017] The contents of fatty acids having 10 to 18 carbon atoms and other fatty acids in 100% by mass of all fatty acids constituting the polyglycerol fatty acid ester refer to the contents in 100% by mass of fatty acids that are raw materials for producing the polyglycerol fatty acid ester. These contents may be measured by carrying out the following steps (1) to (3) on the produced polyglycerol fatty acid ester.
[0018] (1) Sample preparation Prepare the sample according to "2.4.1.2-1996 Methyl esterification method (boron trifluoride methanol method)" in "Standard Methods for Analysis of Fats, Oils and Related Compounds (I)" (compiled by the Japan Oil Chemists' Society).
[0019] (2)Measurement method The measurement shall be made in accordance with "2.4.2.2-1996 Fatty Acid Composition (FID Temperature Programmed Gas Chromatography)" of "Standard Test Methods for the Analysis of Fats, Oils and Related Materials (I)" (compiled by the Japan Oil Chemists' Society).
[0020] (3) Quantification The percentage of each peak area relative to the total peak area recorded by the data processor is taken as the content of the constituent fatty acids.
[0021] Among (B) used in the present invention, one or more selected from the group consisting of dialkyl(meth)acrylamides, dialkylaminoethyl(meth)acrylamides, dialkylaminopropyl(meth)acrylamides, dialkylaminoethyl(meth)acrylates, and dialkylaminopropyl(meth)acrylates (hereinafter also referred to as "B component"), examples of dialkyl(meth)acrylamides include N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, etc. These dialkyl(meth)acrylamides can be used in combination of at least one type or two or more types.
[0022] Among the B components, examples of dialkylaminoethyl(meth)acrylamides include N,N-dimethylaminoethyl(meth)acrylamide, N,N-diethylaminoethyl(meth)acrylamide, etc. These dialkylaminoethyl(meth)acrylamides can be used alone or in combination of two or more.
[0023] Among the B components, examples of dialkylaminopropyl(meth)acrylamides include N,N-dimethylaminopropyl(meth)acrylamide, N,N-diethylaminopropyl(meth)acrylamide, etc. These dialkylaminopropyl(meth)acrylamides can be used alone or in combination of two or more.
[0024] Among the B components, examples of the dialkylaminoethyl (meth)acrylate include N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, etc. These dialkylaminoethyl (meth)acrylates can be used alone or in combination of two or more.
[0025] Among the B components, examples of the dialkylaminopropyl (meth)acrylate include N,N-dimethylaminopropyl (meth)acrylate, N,N-diethylaminopropyl (meth)acrylate, etc. These dialkylaminopropyl (meth)acrylates can be used alone or in combination of two or more.
[0026] Examples of (C): polymerizable monomer having 4 or more ethylene glycols and 1 or more (meth)acryloyl groups in one molecule (hereinafter also referred to as "component C") used in the present invention include polyethylene glycol di(meth)acrylate, EO-modified trimethylolpropane tri(meth)acrylate, EO-modified pentaerythritol tetra(meth)acrylate, EO-modified dipentaerythritol hexa(meth)acrylate, etc. These polymerizable monomers having 4 or more ethylene glycols and 1 or more (meth)acryloyl groups in one molecule can be used alone or in combination of two or more.
[0027] The number of ethylene glycol groups in one molecule of Component C is not particularly limited as long as it is 4 or more, but from the viewpoint of the durability of the anti-fogging properties of the resin composition of the present invention, it is preferably 90 or less, more preferably 35 or less.
[0028] The (D) photopolymerization initiator (hereinafter also referred to as "component D") used in the present invention is a polymerizable initiator that generates radicals when exposed to active energy rays such as ultraviolet rays, and examples thereof include 1-hydroxycyclohexyl phenyl ketone, 2,2-dimethoxy-2-phenylacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2,4,6-trimethylbenzoylphosphine oxide, etc. These photopolymerization initiators can be used alone or in combination of two or more.
[0029] The resin composition of the present invention may contain a polymerizable monomer and / or oligomer having one or more (meth)acryloyl groups (hereinafter also referred to as "component E") other than components B and C. Component E is a substance that controls or supplements the physical properties of the cured product obtained by curing the resin composition of the present invention. Component E may be appropriately selected depending on the properties, shape, application, etc. required for the cured product.
[0030] Examples of the E component include (meth)acrylic acid esters, urethane acrylates, epoxy acrylates, polyester acrylates, polyether acrylates, etc. Examples of the (meth)acrylic acid esters include 2-hydroxy(meth)acrylates, tetrahydrofurfuryl(meth)acrylates, 1,6-hexanediol di(meth)acrylates, triethylene glycol di(meth)acrylates, ethylene oxide-modified bisphenol A di(meth)acrylates, trimethylolpropane tri(meth)acrylates, pentaerythritol tetra(meth)acrylates, dipentaerythritol hexa(meth)acrylates, pentaerythritol tri(meth)acrylates, etc.
[0031] The amount of component A in the resin composition of the present invention is not particularly limited, but is preferably 0.5 to 5 parts by mass, and more preferably 1.0 to 3.5 parts by mass, per 100 parts by mass of the total of components B and C, or components B, C and E.
[0032] The amount of component B in the resin composition of the present invention is not particularly limited, but is preferably 5 to 50 parts by mass, and more preferably 10 to 40 parts by mass, per 100 parts by mass of the total of components B and C, or components B, C and E.
[0033] The amount of component C in the resin composition of the present invention is not particularly limited, but is preferably 5 to 70 parts by mass, and more preferably 20 to 40 parts by mass, per 100 parts by mass of the total of components B and C, or components B, C and E.
[0034] The amount of component D in the resin composition of the present invention is not particularly limited, but is preferably 1.0 to 8.0 parts by mass, and more preferably 3.0 to 6.0 parts by mass, per 100 parts by mass of the total of components B and C, or components B, C and E.
[0035] The resin composition of the present invention may contain the above-mentioned component E, and the amount of component E may be appropriately adjusted depending on the properties, shape, application, etc. of the cured product of the resin composition. The amount of component E is preferably 10 to 90 parts by mass, more preferably 20 to 70 parts by mass, per 100 parts by mass of the total of components B, C, and E.
[0036] The resin composition of the present invention may contain other substances within a range that does not impair the effects of the present invention. Examples of other substances include organic solvents. Examples of organic solvents include methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, isopropyl alcohol, propylene glycol monomethyl ether, toluene, and xylene. These organic solvents dilute the A component, the B component, the C component, and the D component, or the A component, the B component, the C component, the D component, and the E component. When these organic solvents are contained, it is necessary to remove the organic solvent by a method such as drying before curing the resin composition of the present invention with active energy rays, which will be described later.
[0037] The resin composition of the present invention can be obtained by uniformly mixing components A, B, C, and D, or components A, B, C, D, and E. The mixing can be performed by a known mixing method and a known mixing device.
[0038] The temperature at which the components are mixed uniformly is not particularly limited, but it is preferable to heat the components to a temperature that does not affect the components, for example, 80°C or lower, preferably room temperature (25°C) to 60°C.
[0039] A cured resin product obtained by curing the resin composition of the present invention by irradiation with active energy rays (hereinafter, also referred to as "cured resin product of the present invention") is also one aspect of the present invention.
[0040] The active energy rays are not particularly limited as long as they are rays that can cure the resin composition of the present invention, and examples thereof include ultraviolet rays, electron beams, X-rays, etc., and ultraviolet rays are preferred in consideration of polymerizability, ease of handling, etc. The source of ultraviolet rays is not particularly limited, and examples thereof include electrodeless lamps, high-pressure mercury lamps, metal halide lamps, xenon lamps, etc.
[0041] The amount of irradiation of active energy rays varies depending on the types and amounts of each component contained in the resin composition of the present invention, or on the irradiating device, and therefore needs to be appropriately adjusted. For example, the cumulative light amount is 300 to 3,000 mJ / cm. 2 Examples include:
[0042] The cured resin product of the present invention can be obtained by applying the resin composition of the present invention to the surface of a substrate such as a polymeric material or glass, and irradiating the surface with active energy rays.
[0043] Examples of the polymeric material include thermoplastic plastics, thermosetting plastics, other resin materials, etc. The form of these polymeric materials is not particularly limited, but examples thereof include forms such as sheets, films, and molded products.
[0044] The coating method is not particularly limited, and examples thereof include bar coating, roll coating, die coating, spray coating, and dip coating.
[0045] The uses of the resin cured product of the present invention are not particularly limited, and in the electrical materials field, for example, displays, touch panels, housings for mobile devices and home appliances, etc. can be mentioned; in the building materials field, for example, fittings, wall materials, furniture, bathtub mirrors, doorknobs, switches, handrails, window glass, show windows, convex mirrors, etc. can be mentioned; in the automotive field, for example, headlamp lenses, instrument panels such as dashboards, navigation panels, meter panels, etc. can be mentioned; and in the hygiene field, for example, face shields, mouth shields, partitions, glasses, goggles, helmet shields, etc. can be mentioned.
[0046] The present invention will be described below with reference to examples, which are merely illustrative of the present invention and are not intended to limit the present invention. EXAMPLES
[0047] <Preparation of active energy ray-curable resin composition> (1) Raw materials [Component A] A-1 (product name: Poem DL-100; average degree of polymerization of polyglycerin: 2; main constituent fatty acid: lauric acid; manufactured by Riken Vitamin Co., Ltd.) A-2 (product name: Poem DM-100; average degree of polymerization of polyglycerin: 2; main constituent fatty acid: myristic acid; manufactured by Riken Vitamin Co., Ltd.) [B component] B-1 (trade name: DMAA; N,N-dimethylacrylamide; manufactured by KJ Chemicals) B-2 (Product name: DEAA; N,N-diethylacrylamide; manufactured by KJ Chemicals) B-3 (trade name: DMAPAA; N,N-dimethylaminopropylacrylamide; manufactured by KJ Chemicals) [C component] C-1 (product name: NK Ester A-600; 13EO diacrylate; manufactured by Shin-Nakamura Chemical Co., Ltd.) C-2 (product name: NK Ester AT-20E; trimethylolpropane-20EO-triacrylate; manufactured by Shin-Nakamura Chemical Co., Ltd.) C-3 (product name: NK Ester A-DPH-12E; dipentaerythritol-12EO-hexaacrylate; manufactured by Shin-Nakamura Chemical Co., Ltd.) [D component] D-1 (product name: Omnirad 184; 1-hydroxycyclohexyl phenyl ketone; manufactured by IGM) [E component] E-1 (product name: Aronix M-305; pentaerythritol triacrylate; manufactured by Toagosei Co., Ltd.) E-2 (product name: Aronix M-400; dipentaerythritol hexaacrylate; manufactured by Toagosei Co., Ltd.) E-3 (Product name: Shiko UV-1700B; 10-functional urethane acrylate; manufactured by Mitsubishi Chemical Corporation) [Organic solvents] Propylene glycol monomethyl ether (Fujifilm Wako Pure Chemical Industries, Ltd.)
[0048] (2) Combination The formulations of the active energy ray-curable resin compositions prepared using the above raw materials are shown in Tables 1 and 2.
[0049] [Table 1]
[0050] [Table 2]
[0051] (3) Method for preparing active energy ray-curable resin composition Using the same amounts of raw materials shown in Tables 1 and 2, active energy ray-curable resin compositions (Examples 1 to 7, Comparative Examples 1 to 3) were prepared by the following method. Each component was weighed out into a light-shielding container and mixed with a stirrer at 60° C. for 30 minutes to obtain active energy ray-curable resin compositions (Examples 1 to 7, Comparative Examples 1 to 3).
[0052] <<Preparation of resin sheet having coating layer>> (1) Raw materials Resin sheet (polyethylene terephthalate resin sheet; film thickness 100μ; manufactured by Toyobo Co., Ltd.) Active energy ray curable resin composition (Examples 1 to 7, Comparative Examples 1 to 3) (2) Method for producing a resin sheet having a coating layer (2-1) How to make the resin sheet (prototype 1) Example 1 was applied to a resin sheet using a bar coater to a thickness of 10 μm, and then exposed to ultraviolet light (electrodeless lamp; H bulb; illuminance 1400 mW / cm 2 (manufactured by FusionUV) with an integrated light dose of 500 mJ / cm 2 The resin sheet (prototype 1) having a coating layer was obtained by irradiating the resin with ultraviolet light so as to perform photopolymerization. (2-2) Method for producing resin sheets (prototypes 2 to 10) Using a bar coater, one of Examples 2 to 7 and Comparative Examples 1 to 3 was applied to a resin sheet to a thickness of 10 μm / solid content, and the sheet was dried at 90° C. for 3 minutes using a dryer (model: DO-450V; AS ONE Corporation), and then exposed to an ultraviolet lamp (electrodeless lamp; H bulb; illuminance 1400 mW / cm 2 (manufactured by FusionUV) with an integrated light dose of 500 mJ / cm 2 The resin sheets (samples 2 to 10) having a coating layer were obtained by irradiating the resin with ultraviolet light so as to perform photopolymerization.
[0053] <Evaluation of antibacterial, anti-fogging, and antistatic properties of resin sheets with coating layers> (1) Antibacterial properties The antibacterial activity of the obtained resin sheets (samples 1 to 10) against Staphylococcus aureus (NBRC 13276) and Escherichia coli (NBRC 3972) was measured based on the test method described in JIS Z2801 "Antibacterial processed products - Antibacterial test method, antibacterial effect". The results were coded according to the following evaluation criteria. The results are shown in Table 3. ◎: Antibacterial activity value is 4.0 or more (strong antibacterial effect) 〇: Antibacterial activity value is 2.0 or more and less than 4.0 (antibacterial effect) ×: Antibacterial activity value is less than 2.0 (weak antibacterial effect)
[0054] (2) Evaluation of anti-fogging properties A resin sheet (prototypes 1-10) was attached to the top surface of a cylindrical bottomless beaker (Fig. 1) with a slope on the top surface along the slope so that the coating layer was on the inside, and the beaker was placed in a thermostatic water bath filled with water at 50°C so that the bottom surface was immersed in water up to 3 cm. After 1 minute from the placement, the presence or absence of water droplets on the resin sheet was visually observed and evaluated according to the following evaluation criteria. The results are shown in Table 3. ◎: Water droplets adhere to less than 1% of the resin sheet's area (strong anti-fogging effect) 〇: Water droplets adhere to 1% to less than 20% of the resin sheet area (anti-fogging effect) ×: Water droplets adhere to 20% or more of the resin sheet area (weak anti-fogging effect)
[0055] (3) Evaluation of antistatic properties The obtained resin sheets (samples 1 to 10) were aged for 24 hours at 20°C and 65% RH, and the surface resistivity (Ω / □) was measured under the same conditions using an ultra-insulation meter (model: SM-8000 Series; manufactured by HIOKI Corporation). The results are shown in Table 3. ◎: Surface resistivity (Ω / □) is less than 10 to the power of 10 (strong antistatic effect) 〇: Surface resistivity (Ω / □) is greater than 10 to the power of 10 or less (antistatic effect) ×: Surface resistivity (Ω / □) is greater than 10 to the power of 12 (weak antistatic effect)
[0056] [Table 3]
[0057] The results showed that the resin sheets (trial products 1 to 7) using the example products 1 to 7 as the active energy ray-curable resin compositions were rated "Excellent" for antibacterial properties, antifogging properties, and antistatic properties. On the other hand, the resin sheets (prototypes 8 to 10) using comparative examples 1 to 3 as the active energy ray-curable resin compositions were rated "X" for all or any of the antibacterial, antifogging, and antistatic properties, and did not achieve a rating of "O" or above in any of the properties.
Claims
1. An active energy ray-curable resin composition characterized by containing the following (A) to (E), wherein the active energy ray-curable resin composition contains 0.5 to 5 parts by mass of component A, 5 to 50 parts by mass of component B, 5 to 70 parts by mass of component C, and 1.0 to 8.0 parts by mass of component D, relative to a total of 100 parts by mass of components B, C, and E: (A): Polyglycerol fatty acid ester in which the average polymerization degree of the constituent polyglycerol is 2 to 3 and the carbon number of the main constituent fatty acid is 10 to 18. (B): one or more selected from the group consisting of dialkyl(meth)acrylamide, dialkylaminoethyl(meth)acrylamide, dialkylaminopropyl(meth)acrylamide, dialkylaminoethyl(meth)acrylate, and dialkylaminopropyl(meth)acrylate (C): a polymerizable monomer having four or more ethylene glycol groups and one or more (meth)acryloyl groups in one molecule (D): Photopolymerization initiator (E): Polymerizable monomers and / or oligomers having a (meth)acryloyl group other than (B) and (C).
2. A cured resin product obtained by irradiating the active energy ray-curable resin composition according to claim 1 with active energy rays.
Citation Information
Patent Citations
Hydrophilic membrane forming composition, hydrophilic membrane formed, and its preparation
JP1988251401A
Coating agent composition and optical information medium using the same
JP2006152130A
Active energy ray curable antifogging composition and cured article using the same
JP2018090685A
Adhesive film and curable composition for forming adhesive layer
JP2019156916A
Active energy ray-curable antifogging composition and cured product
JP2019210396A